Analysis Of Rice Marketing Channels At PP. Maju Jaya In Ranomeeto Sub-District, South Konawe District - Yuniar Azzahra; Azhar Bafadal; Sitti Aida Adha Taridala (International Journal of Technology and Education Research, 2023)
This study aims to analyze the rice marketing channels and the efficiency of rice marketing in PP. Maju Jaya. This study used a descriptive analysis, margin analysis and marketing efficiency. The determination of the sample of marketing institutions uses the snowball sampling technique to determine the distribution of rice starting from the PP factory. Maju Jaya then looked for distributors involved in distributing the rice. The research that has been carried out obtained the following results; (1) Marketing Channels involved in the rice marketing process from producers to consumers, namely: (a) On channel I PP. Maju Jaya distributes rice directly to Inter Island Traders (b) ) On channel II PP. Maju Jaya distributes rice to wholesalers and then resells it to final consumers and (c) On channel III PP. Maju Jaya distributes rice to wholesalers and then sells it to retailers and resells it to final consumers (2) Percentage of the share of prices received by producers on rice marketing channels by PP. Maju Jaya in channel I is 100%, channel II is 92%, and marketing channel III it is 80% which shows the three marketing channels have been efficient because the percentage of prices received by producers is greater than 50%.